A multimodal microfluidic-based platform integrating topographical and equibiaxial mechanical cues for next-generation in vitro cell microenvironment mimicking - Pagliara, Denise; Vecchione, Raffaele; Mollo, Valentina; Netti, Paolo Antonio (Frontiers in Bioengineering and Biotechnology, 2025)
The cellular microenvironment is a powerful regulator of the cell state and function. Both biochemical and morphophysical environmental cues have been shown to profoundly influence cellular decisions. However, the fundamental principles governing the intricate crosstalk between microenvironmental manipulation and the modulation of cell functions remain largely elusive. To unravel the regulatory role of the microenvironment in determining cellular fate and state, it is essential to develop tools capable of precisely presenting and integrating these signals. In this context, we propose a next-generation cell culture system that synergistically combines microfluidic and biomechanical platforms. This system is designed to systematically deliver microenvironmental stimuli to condition cell state. As a notable use case, we selected cardiomyocytes (CMs) given the well-documented influence of biochemical and morphophysical cues on cardiac tissue homeostasis. The platform features a multilayer design integrating complex mechanical stimulation, such as equibiaxial strain, on a deformable membrane equipped with microchannels for nutrient delivery. A radial micropattern was fabricated on the membrane to guide cell alignment along the direction of stretching, thereby homogenizing cellular response. The functionality of the device was first validated through COMSOL simulations and subsequently experimentally tested to confirm the interplay between equibiaxial mechanical stimulation and fluid flow. When HL-1 rat atrial CMs were seeded on the platform, they proliferated, aligned with the micropattern, and exhibited persistent migration along the stretching direction under equibiaxial deformation. These findings demonstrate that the combination of microenvironmental signals is critical for enhancing cellular activity and underscore the importance of accurately replicating the cell microenvironment in lab-on-chip applications.